Crime Victims Protection in Indonesia: An Analysis of the Recent Victim Protection Acts - Mahfud, Mahfud (Kertha Patrika, 2020)
The Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power (1985) ensures the protection of victims of crime. Basically, the implementation of this international declaration depends on the domestic law of each state.  Indonesia has promulgated Act No. 13 of 2006 concerning Witness and Victim Protection (Witness and Victim Protection Act) and its Amendment (Act No. 31 of 2014) to give protection of the victim, although not fully adopted the principles contained in the declaration. This article aims to analyze the protection of the victims under the recent Indonesian victim protection Acts and to examine to what extent the Acts in line with the declaration. It is a normative legal research that collects sources from libraries, databases, and archives. This research suggested that Witness and Victim Protection Act has provided the protection to the victim that is limited to victims of a grave violation of human rights, terrorism, trafficking, torture, sexual crime, and serious assaults in the form of compensation (only for a grave violation of human rights and terrorism), restitution and certain assistances under the auspices of the Witness and Victim Protection Agency (LPSK). However, this Act is not yet fully in line with the Declaration, particularly with regard to the right of victims to be present in the criminal justice process to express their views when it comes to their personal interests.